Implementation of Game-Based Project-Based Learning Model to Improve The Activeness and Islamic Values of Elementary School Students in Science Subjects - Agung Widyantoro; Nur Samsiyah; Cerianing Putri P; Heny Kusuma (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools is still predominantly conducted through conventional methods, such as assignments and the use of student worksheets, resulting in low student interest and engagement. This study aims to analyze the effectiveness of implementing a game-based project-based learning model in enhancing student learning activity and fostering Islamic values in science lessons. This research is a classroom action research conducted in two cycles, which included the stages of planning, implementation, observation, and reflection. The research subjects consisted of 15 fourth-grade elementary school students. Data were collected through observation and tests, using observation sheets to assess student activity and evaluation tests to measure learning outcomes. Data analysis was carried out through data collection, reduction, presentation, and drawing conclusions. The results showed a 20% increase in student learning activity, a 40% improvement in group collaboration, and a 67% increase in project completion timeliness. Additionally, students were able to compile project reports systematically and demonstrated Islamic values such as cooperation, tolerance, honesty, independence, and responsibility. The study concludes that the game-based project-based learning model is effective in increasing student engagement and fostering Islamic character in science learning. The implication of this study highlights the importance of applying contextual and enjoyable learning approaches to promote active participation and character development in elementary education.